2012
DOI: 10.1179/1743281212y.0000000006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of crystallisation behaviour of mould fluxes on properties of liquid slag film

Abstract: During the continuous casting of medium carbon steel slabs, stable liquid slag film performance is necessary to ensure that the process runs smoothly. In this paper, the effects of mould flux crystallisation behaviour on the properties of leftover liquid slag films were examined. First, the compositions of the leftover liquid slags of high fluorine, CaO-SiO 2 -TiO 2 and CaO-SiO 2 -Na 2 O based mould fluxes after a single crystalline phase was separated were calculated. Then, the viscosity, melting temperature,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…1 In order to determine an appropriate substitute for the cuspidine (3CaO-2SiO 2 -CaF 2 ) mineral for heat transfer control, some different crystalline phases were studied, such as gehlenite (CaO-Al 2 O 3 -SiO 2 ), perovskite (CaO-TiO 2 ), CaO-SiO 2 -Na 2 O (CSN) and CaO-SiO 2 -TiO 2 (CST). [2][3][4] The properties of slags, such as the viscosity and crystallisation behaviour, have been investigated by many metallurgists. The structures of calcium silicate-based slags have been investigated by steelmakers using Fourier transform infrared spectroscopy (FTIR), Raman spectra, nuclear magnetic resonance and other methods.…”
Section: Introductionmentioning
confidence: 99%
“…1 In order to determine an appropriate substitute for the cuspidine (3CaO-2SiO 2 -CaF 2 ) mineral for heat transfer control, some different crystalline phases were studied, such as gehlenite (CaO-Al 2 O 3 -SiO 2 ), perovskite (CaO-TiO 2 ), CaO-SiO 2 -Na 2 O (CSN) and CaO-SiO 2 -TiO 2 (CST). [2][3][4] The properties of slags, such as the viscosity and crystallisation behaviour, have been investigated by many metallurgists. The structures of calcium silicate-based slags have been investigated by steelmakers using Fourier transform infrared spectroscopy (FTIR), Raman spectra, nuclear magnetic resonance and other methods.…”
Section: Introductionmentioning
confidence: 99%
“…For casting high-Ti steels with CaO-SiO 2 -based mold fluxes, F has been replaced with TiO 2 to generate the perovskite primary crystal phase, thereby substituting the cuspidine phase to control the heat transfer. 27,125,126) It has been speculated that TiO 2 reduces the infrared transmittance of the slag film and inhibits radiation heat transfer. In addition, Nakada and Nagata 127) also observed that the incubation time for titanite (CaSiTiO 5 ) nucleation in CaO-SiO 2 -TiO 2 slags was comparable to that of the cuspidine phase in commercial mold fluxes, which suggests that the CaSiTiO 5 could also crystallize rapidly in slag films similar to cuspidine in commercial mold fluxes.…”
Section: Crystallization Behaviormentioning
confidence: 99%
“…Experimental samples were prepared using analytical-grade reagents (CaCO 3 , SiO 2 , Na 2 CO 3 , CaF 2 , and Al 2 O 3 ). The physical properties were measured (see Table 2) [20][21][22]. The melting temperature was measured by the hemisphere point method; the high temperature viscosity and viscosity-temperature curve were measured by a high-temperature rotational viscometer (using graphite bobs with 15 mm diameter and graphite crucibles with 55 mm inner diameter).…”
Section: Mold Flux Selection and Slag Film Acquisitionmentioning
confidence: 99%